Novel Salinomycin-Based Paramagnetic Complexes-First Evaluation of Their Potential Theranostic Properties - Irena Pashkunova-Martic; Rositsa Kukeva; Radostina Stoyanova; Ivayla Pantcheva; Peter Dorkov; Joachim Friske; Michaela Hejl; Michael Jakupec; Mariam Hohagen; Anton Legin; Werner Lubitz; Bernhard K. Keppler; et al. (MDPI AG, 2022)
Combining therapeutic with diagnostic agents (theranostics) can revolutionize the course of malignant diseases. Chemotherapy, hyperthermia, or radiation are used together with diagnostic methods such as magnetic resonance imaging (MRI). In contrast to conventional contrast agents (CAs), which only enable non-specific visualization of tissues and organs, the theranostic probe offers targeted diagnostic imaging and therapy simultaneously. Methods: Novel salinomycin (Sal)-based theranostic probes comprising two different paramagnetic metal ions, gadolinium(III) (Gd(III)) or manganese(II) (Mn(II)), as signal emitting motifs for MRI were synthesized and characterized by elemental analysis, infrared spectral analysis (IR), electroparamagnetic resonance (EPR), thermogravimetry (TG) differential scanning calorimetry (DSC) and electrospray ionization mass spectrometry (ESI-MS). To overcome the water insolubility of the two Sal-complexes, they were loaded into empty bacterial ghosts (BGs) cells as transport devices. The potential of the free and BGs-loaded metal complexes as theranostics was evaluated by in vitro relaxivity measurements in a high-field MR scanner and in cell culture studies. Results: Both the free Sal-complexes (Gd(III) salinomycinate (Sal-Gd(III) and Mn(II) salinomycinate (Sal-Mn(II)) and loaded into BGs demonstrated enhanced cytotoxic efficacy against three human tumor cell lines (A549, SW480, CH1/PA-1) relative to the free salinomycinic acid (Sal-H) and its sodium complex (Sal-Na) applied as controls with IC50 in a submicromolar concentration range. Moreover, Sal-H, Sal-Gd(III), and Sal-Mn(II) were able to induce perturbations in the cell cycle of treated colorectal and breast human cancer cell lines (SW480 and MCF-7, respectively). The relaxivity (r1) values of both complexes as well as of the loaded BGs, were higher or comparable to the relaxivity values of the clinically applied contrast agents gadopentetate dimeglumine and gadoteridol. Conclusion: This research is the first assessment that demonstrates the potential of Gd(III) and Mn(II) complexes of Sal as theranostic agents for MRI. Due to the remarkable selectivity and mode of action of Sal as part of the compounds, they could revolutionize cancer therapy and allow for early diagnosis and monitoring of therapeutic follow-up.